Bell Popcorn by A&H / Muhammad Alif Syazwan Abu Bakar and Mohamad Haziq Mohamad Rosli - Abu Bakar, Muhammad Alif Syazwan; Mohamad Rosli, Mohamad Haziq (2022)
The main objective that is to achieve for the business is to offer a special fully coated caramel popcorn made in Malaysia to our customer with affordable price and luxurious taste of popcorn. Our business was started on 25 April 2022. According to the customer review, our product gave a fantastic taste because of the caramel taste and the type of popcorn make our customer remembered the taste. This product is also liked by many group of ages due to the cheap and affordable price. Hence, this product provides a good insight for the continuation of sale to our customers. Since early of the opening, Bell Popcorn by A&H was getting a lot of order my friends and family members. Increasing demands for our product results into a good profitable sale revenue to our business project. Therefore, Bell Popcorn A&H is a good marketable product of choice that can be further expanded to many different areas as the business keep on growing.